PENGARUH PENGGUNAAN HYDROCARBON CRACK SYSTEM (HCS) DENGAN VARIASI BAHAN BAKAR BENSIN TERHADAP TORSI DAN DAYA SEPEDA MOTOR SUZUKI SATRIA FU150 - Wahyu Kurnialy; Husin Bugis; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
This research aims to investigate the effect of Hydrocarbon Crack System (HCS) on torque and power of Suzuki Satria FU150 motorcycle and the effect of HCS with variation of gasoline (Premium, Pertalite and Pertamax) on torque and power of Suzuki Satria FU150 motorcycle. This research was conducted in Automotive Laboratory of Mechanical Engineering Education Faculty of Teacher Training and Education Sebelas Maret University Surakarta and at PT. Motocourse Technology (MOTOTECH). This type of research is experiment research with quantitative approach. The sample of this research is Suzuki Satria FU150  with serial police number R 2764 BM The sampling obtainable using purposive sampling technique. The data obtained from the torque and power engine measurement using dynotest. Based on the research result, it concluded that there is an effect of using Hydrocarbon Crack System (HCS) to torque and power of Suzuki Satria FU150. The use HCS with Pertamax is the most increasing the torque and power if compared to Premium and Pertalite.